Financial systems and economic growth: Empirical evidence from Australia - Sheilla Nyasha; Nicholas M. Odhiambo (Contemporary Economics, 2016)
This paper examines the dynamic impact of both bank- and market-based financial development on economic growth in Australia during the period from 1980 to 2012. The study uses the autoregressive distributed lag (ARDL) bounds testing approach to examine this linkage. Unlike certain previous studies, this study uses both bank- and market-based financial development indices to measure the level of financial sector development in Australia. These indices were computed using the means-removed average method. The empirical results of this study show that while bankbased financial development has a short-run positive impact on economic growth in Australia, market-based financial development has no significant impact on economic growth, both in the short run and in the long run. These results imply that, in Australia, it is of paramount importance to concentrate on pro-banking sector policies, at least in the short run, to stimulate growth.
Keywords: G10; G20; O16; 330; Australia; bank-based financial development; market-based financial development; economic growth